Editorial. In and out of the museum: new destinations of the moving image - Santos, Luísa (2022)
Issue 04 of The Garage Journal publishes innovative scholarship on the relationship between the moving image and the museum. It analyzes ways in which cinema, video art, and curatorial practices inform and influence each other. Dissecting this intricate relationship, the issue challenges traditional assumptions and opens up a discourse where affinities and oppositions coexist.